Evaluation of FESOM2.0 Coupled to ECHAM6.3: Preindustrial and HighResMIP Simulations. (25th November 2019) - Sidorenko, D.; Goessling, H.F.; Koldunov, N.V.; Scholz, P.; Danilov, S.; Barbi, D.; Cabos, W.; Gurses, O.; Harig, S.; Hinrichs, C.; Juricke, S.; Lohmann, G.; et al.
Abstract: A new global climate model setup using FESOM2.0 for the sea ice‐ocean component and ECHAM6.3 for the atmosphere and land surface has been developed. Replacing FESOM1.4 by FESOM2.0 promises a higher efficiency of the new climate setup compared to its predecessor. The new setup allows for long‐term climate integrations using a locally eddy‐resolving ocean. Here it is evaluated in terms of (1) the mean state and long‐term drift under preindustrial climate conditions, (2) the fidelity in simulating the historical warming, and (3) differences between coarse and eddy‐resolving ocean configurations. The results show that the realism of the new climate setup is overall within the range of existing models. In terms of oceanic temperatures, the historical warming signal is of smaller amplitude than the model drift in case of a relatively short spin‐up. However, it is argued that the strategy of "de‐drifting" climate runs after the short spin‐up, proposed by the HighResMIP protocol, allows one to isolate the warming signal. Moreover, the eddy‐permitting/resolving ocean setup shows notable improvements regarding the simulation of oceanic surface temperatures, in particular in the Southern Ocean. Key Points: A new climate model setup using an unstructured‐mesh ocean‐sea ice component has been developed Mean state and long‐term drift under preindustrial climate conditions are evaluated Modeled climates using coarse and eddy‐resolving ocean configurations are compared